Intestinal Flora: A Potential Mechanism by Which Yinlai Decoction Treats Lipopolysaccharide-Induced Pneumonia. (23rd March 2022) - Xu, Jingnan; Ma, Xueyan; Bai, Chen; Jiang, Xin; Huang, Ling; Gao, Fei; Li, Yini; Yu, He; Liu, Tiegang; Gu, Xiaohong
Abstract : Background . We intended to explore the mechanism of Yinlai decoction in the treatment of lipopolysaccharide (LPS)-induced pneumonia from the perspective of intestinal flora. Methods . Thirty Sprague–Dawley rats were randomly assigned to the blank control group (N), the pneumonia group (P), and the Yinlai decoction group (PT). The rat pneumonia model was established using LPS inhalation (0.5 mg/mL, 5 mL, 30 min/day, 3 days). Yinlai decoction was administered intragastrically (2 mL/100 g, 3 days). Lung tissue pathology, organ indexes, serum inflammatory factors, tumor necrosis factor-alpha (TNF- α ), and intestinal flora changes were measured. Results . Lung tissue inflammation was prevented by Yinlai decoction. IL-6 levels showed a higher tendency to be higher, and IL-12 and TNF- α were significantly higher in the PT group than in the P group. The structure of the intestinal flora in the P differed from that in the N. The relative abundance of 10 out of 12 microflora was significantly higher in the P group than in the N and PT groups. In the PT group, the structure and the distribution of microbial groups were like those of the N group. Conclusions . Yinlai decoction inhibited LPS-induced lung and systemic inflammation in rats and may help the intestinal flora restore equilibrium by inhibiting the colonization of pathogenic bacteria and adjusting the ratio between probiotics and pathogenic bacteria. Intestinal flora may serve as a mediator of Yinlai decoction's effect on LPS-induced pneumonia.